DESCRIPTION OF MATHEMATICS PROBLEM SOLVING ABILITY BASED ON COGNITIVE LEARNING STYLE OF XI CLASS STUDENTS AT SENIOR HIGH SCHOOL 19 GOWA - Resmi Mursal; A Husniati; Erni Ekafitria Bahar (JURNAL NALAR PENDIDIKAN, 2023)
This study aims to determine the description of the ability of students of class XI SMA Negeri 19 Gowa in solving math problems based on their learning style is the main focus of this research. The research subjects were 2 students, namely 1 student cognitive style field dependent and 1 student cognitive style field independent. The researcher is the main instrument with supporting instruments namely GEFT test sheet, problem solving proficiency test sheet, and interview guide. The conclusions of this study are: (1) the subject's problem solving ability with field dependent cognitive style is still lacking because the subject can understand the problem presented but has not been able to formulate a solution plan appropriately and has not been able to implement the solution plan. Subjects also have not been able to do a careful recheck; (2) Subject problem solving ability with cognitive field independent style is very good because the subject is able to interpret the problem neatly and able to formulate a good solution plan, and can apply every step of the solution that has been designed. The subject is also able to re-evaluate each stage of the solution so that the subject is confident in the correctness of his answer.